Evaluation of Confining Pressure Models for Circular Concrete-Filled Steel Tube Short Columns under Concentric Loading - Le, Hoang An (Engineering, Technology & Applied Science Research, 2023)
It is well known that the confinement effect provided by the steel tube significantly increases the strength and ductility of circular Concrete Filled Steel Tube (CFST) columns under concentric loading. The lateral pressure is an important factor to calculate the strength enhancement of CFST columns. To reliably predict the ultimate strength of circular CFST columns, many models have been developed for predicting the lateral pressure due to the confinement effect. This paper aims to evaluate some of these confining pressure models. The values of the compressive strength of confined concrete and lateral confining pressure of circular CFST short columns were calculated using these existing models and were compared with those obtained from previous test results. In addition, a comparison between the ultimate loads predicted by these models and by Eurocode 4 (EC4) was carried out. Based on the comparison results, some suitable models for circular CFST short columns with the use of normal-strength, high-strength, and ultra-high-strength concrete were indicated.